Occident - Orient : L'Art Moderne et l'Art Islamique. - Beyer, Victor; Berk, Nurullah (Strasbourg : Ville de Strasbourg, 1972)
Atlan, Jean-Michel ; Balla, Giacomo ; Baumeister, Willi ; Bazaine, Jean ; Beaudin, A. ; Bill, Max ; Bissière, Roger ; Brancusi, Constantin ; Van Breedam, Camiel ; Caulfield, Patrick ; Cohen, B. ; Delaunay, Sonia ; Dufy, Raoul ; Friedeberg, Pedro ; Gleizes, Albert ; Golyscheff, Jefim ; Hartung, Hans ; Herbin, Auguste ; Kandinsky, Wassily ; Klee, Paul ; Klimt, Gustav ; Kupka, Frantisek ; Lapique, Charles ; Van Lint, Louis ; Lurçat, Jean ; Macke, August ; Matisse, Henri ; Miro, Joan ; Morellet, François ; Peeters, J. ; Picabia, Francis ; Picasso, Pablo ; Seuphor, Michel ; Stoffel, M. ; Tomlin, Bradley Walker ; Vedova, Emilio ; Vieira da Silva, Maria Elena ; Zenderoudi, Hossein
Occident - Orient : L'Art Moderne et l'Art Islamique, a l'Ancienne Douane, Strasbourg, 15 mai - 15 septembre 1972
kunstcatalogus